Do we Get More Points if we Take Bigger Risks? Modeling Boundary-Setting in the Undergraduate Acting Classroom - Nicolas Shannon Savard (The Journal of Consent-Based Performance, 2023)
Building from the ideas and practices of Theatrical Intimacy Education which provide guidance on how to set and communicate boundaries, this essay will outline some tools that may help educators and directors facilitate frank and open conversations about the decision-making processes that go into boundary-setting and giving informed consent. The article lays out how Theatrical Intimacy Education’s work around consent and boundaries may be put into productive conversation with applied theatre’s work around risk. The author describes the ways that they have engaged in conversations with their own undergraduate acting students about risk and boundary-setting in the context of devised performance. Finally, combining concepts from intimacy direction, applied theatre, and trial-and-error pedagogical praxis, they propose a framework and tool that theatre educators and directors might use to facilitate conversations about risk, boundaries, and consent in their own classrooms.